PEMENUHAN HAK ANAK DI INDONESIA MELALUI PERENCANAAN PENGASUHAN, PENGASUHAN TUNGGAL DAN PENGASUHAN BERSAMA - Saraswati, Rika; Boputra, Emanuel; Kusniati, Yuni (Veritas et Justitia, 2021)
In many countries, joint custody has replaced and is considered better than sole custody. It is also deemed more in line with the gender equality principle which demands both parents to share responsibility for the custody and care of the child post-divorce. This article discusses how judges in divorce cases decide on child custody, and the extent to which they consider the merits of joint or sole custody and demand divorcees to consider making a parenting plan in the best interest of their children.  Qualitative data is collected from the District Court and Religious Court at Semarang and by analysing 4 court decisions regarding child custody.  Interestingly, none of the Courts above possess or implements a policy or have some procedural ruling obligating judges in divorce cases to demand parents to consider joint custody or making a parenting plan post-divorce. Obligatory pre-trial mediation is geared more as a procedural-formalistic attempt to dissuade parties to continue with divorce.